Does "Islamophobia" curtail free speech? - Rumy Hasan (Institute of Economic Affairs (IEA), 2022)
While the offence of blasphemy has been abolished, the Racial and Religious Hatred Act, despite its protection for freedom of expression, is nevertheless, regressive. Without proper scrutiny or debate, the epithet 'Islamophobia' has seamlessly become accepted as a valid phenomenon and term in mainstream society. This is doubtless considered a success for those Islamic organisations and campaigners that easily take offence, and their apologists, but it is decidedly harmful to free speech, the bedrock of a free society.
Keywords: 330